2001
DOI: 10.1017/s0033291701003488
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated psychosis: a critical examination of the concept and its importance

Abstract: It is important that there should be more thorough investigations of DUP, its correlates, and the extent to which it does mediate any advantages of earlier intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
346
3
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(380 citation statements)
references
References 71 publications
17
346
3
14
Order By: Relevance
“…Notwithstanding this issue, the current findings suggest that the significance of minimising the duration of untreated psychosis (DUP) in first episode psychosis Norman and Malla, 2001;Norman et al, 2005), as recently observed again in the RAISE study (Kane et al, 2015), may also be critical in the UHR population in the form of minimising the duration of untreated illness (DUI). That is, identifying and providing intervention as early as possible in the course of attenuated psychotic symptoms may have an impact on the trajectory of illness, averting the transition to fullyfledged psychotic disorder.…”
Section: Discussionmentioning
confidence: 62%
“…Notwithstanding this issue, the current findings suggest that the significance of minimising the duration of untreated psychosis (DUP) in first episode psychosis Norman and Malla, 2001;Norman et al, 2005), as recently observed again in the RAISE study (Kane et al, 2015), may also be critical in the UHR population in the form of minimising the duration of untreated illness (DUI). That is, identifying and providing intervention as early as possible in the course of attenuated psychotic symptoms may have an impact on the trajectory of illness, averting the transition to fullyfledged psychotic disorder.…”
Section: Discussionmentioning
confidence: 62%
“…There are at least two clinical reasons to emphasize early detection of schizophrenia: the growing evidence that by intervening in the early stages of psychosis, clinicians may be able to improve longer-term outcomes [3][4][5], and the equally important idea that early detection can result in an immediate reduction of suffering, regardless of any effects further downstream. Unfortunately, people experiencing early psychotic symptoms rarely seek treatment on their own.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent strands of evidence have concentrated attention on pathways to care in psychosis: one that certain ethnic groups experience adverse pathways into care (Bhui et al, 2003), (Morgan et al, 2005, Morgan et al, 2005b and second, that reducing treatment delays may improve outcomes in early psychosis (Norman and Malla, 2001). Early intervention strategy is based upon the presupposition that at least some reasons for treatment delay are malleable and could be targeted for intervention.…”
Section: Introductionmentioning
confidence: 99%